Upaya Pencegahan Hipertensi Melalui Program ‘MARI GASI’ di Wilayah Kerja Puskesmas Pangkalan - Kamal Kasra; Nadifah Khairini Fahdi; Muhamad Farhan; Nurul Aulia Putri; Sinta Oktafiani; Fritiara Fritiara; Asha Firnandia; Rezi Fatrima Surya (Warta Pengabdian Andalas)
Hypertension or high blood pressure is one of the significant health problems in the world, including in Indonesia. The prevalence of hypertension in Lima Puluh Kota Regency in 2022 reached 15% or 10,688 out of 70,250 people who took blood pressure measurements. However, only 627 people (11.8%) took blood pressure measurements and received hypertension services according to standards. Therefore, it is necessary to increase public knowledge about hypertension. This service activity was carried out in September 2023 through the emo-demo method, which expects health promotion efforts through an emotional approach. The service activities were carried out on 37 community members, and it was found that there was an increase in the average score of community knowledge from 51.56 to 90.63. An increase can follow this increase in community knowledge, attitudes, and actions toward efforts to prevent and control hypertension, including the prevention of complications of hypertension in the community.